2020
DOI: 10.1007/s00268-020-05760-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Emergency General Surgery During Covid‐19 in Scotland: A Prospective Cohort Study

Abstract: Introduction Covid-19 has had a significant impact on all aspects of health care. We aimed to characterise the trends in emergency general surgery at a district general hospital in Scotland. Methods A prospective cohort study was performed from 23/03/20 to 07/05/20. All emergency general surgery patients were included. Demographics, diagnosis and management were recorded along with Covid-19 testing and results. Thirty-day mortality and readmission rates were also noted. Similar data were collected on patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
41
2
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 26 publications
12
41
2
5
Order By: Relevance
“…When it comes to reducing collateral damage and prognostic disadvantages caused by the pandemic, a key role is played by dedicated patient education and by ensuring the least possible changes to emergency surgical care [ 30 ]. It is undoubtedly essential to emphasize that, in the changed clinical care situation as a result of the pandemic measures, it is crucial to identify patients requiring an emergency operation without delay despite changed circumstances [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…When it comes to reducing collateral damage and prognostic disadvantages caused by the pandemic, a key role is played by dedicated patient education and by ensuring the least possible changes to emergency surgical care [ 30 ]. It is undoubtedly essential to emphasize that, in the changed clinical care situation as a result of the pandemic measures, it is crucial to identify patients requiring an emergency operation without delay despite changed circumstances [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the usually low rate of very complicated cases of appendicitis does not allow an uncritical extrapolation of the current results to other surgical emergencies. A comparison with the international literature shows some parallels regarding a reduction in appendectomies [ 13 , 14 ], a later presentation, and an increased inflammatory reaction [ 5 , 15 – 18 , 20 , 31 ]. The international survey of Ielpo et al of more than 700 surgeons worldwide reported a decrease of appendicitis and an increase of complicated cases based on a questionnaire [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations